Peningkatan Kesejahteraan Ibu Hamil dengan Prenatal Yoga - Astuti, Yuni; Afsah, Yusi Riwayatul (Uhamka Press, 2019)
Pregnant women experience physical and psychological changes during the pregnancy process. Physical changes impact the mother experiencing several complaints of back pain, weakness body, and tired easily. Based on the interviews with health volunteers in the Gejawan Wetan and Gejawan Kulon region found that pregnant women complain of stiffness in the body frequently. In addition, pregnant women in this region have never participated in exercise during their pregnancy. The program to reduce this problem is giving health education about adaptation in pregnant women, activities during pregnancy and prenatal yoga for pregnant women. After participating in this program, it is expected that pregnant women can overcome their complaints during pregnancy by doing some activities which are suitable for pregnant women and doing prenatal yoga exercises as well. Therefore, with those activities, the back pain among pregnant women can be reduced so that the quality of life of pregnant women can be improved